2006
DOI: 10.1080/13548500500159430
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to HAART: Perspectives from clients in treatment support programs

Abstract: The development of highly active antiretroviral therapy (HAART) has resulted in dramatic decreases in morbidity and mortality for HIV-infected individuals. Because the long-term efficacy of HAART is dependent on near perfect adherence, many providers offer services to support adherence, including education, regimen review, counseling, and reminder tools. Little is known regarding the utilization or efficacy of these services. In this paper, we report on data collected during 32 open-ended interviews conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 38 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…All studies were conducted in a single country. Twelve studies were conducted in high-income countries (HICs: Canada and United States) [33,34,40,4446,4852,56], 13 in middle-income countries (MICs: Brazil, China, India, Nigeria, Peru, Romania, South Africa, Swaziland, Thailand and Zambia) [15,17,3032,36,38,4143,47,53,54] and six in low-income countries (LICs: Mozambique, Rwanda, Tanzania, Uganda and Zimbabwe) [16,29,35,37,55]. The overall studies focused on children living with HIV (two studies) [30,54], adolescents (four studies) [43,45,48,53], adults (21 studies) [15,1637,3941,44,46,4952,54,56] and pregnant women (one study) [55].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were conducted in a single country. Twelve studies were conducted in high-income countries (HICs: Canada and United States) [33,34,40,4446,4852,56], 13 in middle-income countries (MICs: Brazil, China, India, Nigeria, Peru, Romania, South Africa, Swaziland, Thailand and Zambia) [15,17,3032,36,38,4143,47,53,54] and six in low-income countries (LICs: Mozambique, Rwanda, Tanzania, Uganda and Zimbabwe) [16,29,35,37,55]. The overall studies focused on children living with HIV (two studies) [30,54], adolescents (four studies) [43,45,48,53], adults (21 studies) [15,1637,3941,44,46,4952,54,56] and pregnant women (one study) [55].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies provided detailed experiences of PLHIV [15,17,29,3237,39,40,4446,4856]. Thirteen studies explored the experiences of healthcare providers and lay health workers in addition to the experiences of PLHIV [15,16,31,33,35,37,38,4143,47,54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Social support PLWH who report high levels of social support from family, friends, or healthcare providers are more likely to adhere than those with lower levels of support (Barclay et al, 2007;Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Gonzalez, Penedo, Dur, Antoni, & Horne, 2007;Langebeek et al, 2014;Simoni, Frick, & Huang, 2006;Weiss et al, 2006). Whereas some researchers identified a direct relationship between social support and medication adherence (Gonzalez et al, 2007), others found that the relationship between social support and medication adherence is mediated by other factors, such as depression and self-efficacy (Simoni et al, 2006).…”
Section: Patient-provider Communicationmentioning
confidence: 92%
“…50, 52, 53 In this study, participant connection with other students may have motivated them to attend classes more frequently. Although some degree of both instructor and social support would have been inherent to predetermined cohorts and hospital-situated classes, the level of support in this study was enhanced by the community-based classes, thus underscoring the influence of the pragmatically delivered Tai Chi intervention.…”
Section: Discussionmentioning
confidence: 91%
“…Several qualitative studies exploring adherence have demonstrated that forming supportive bonds with instructors has a positive influence on adherence to a variety of interventions including exercise programs and medication regimens. 5053 …”
Section: Discussionmentioning
confidence: 99%